2017
DOI: 10.1039/c7cc02504a
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to air boosts CuAAC reactions catalyzed by PEG-stabilized Cu nanoparticles

Abstract: New PEG-stabilized CuNP catalysts are designed upon Cu(ii) reduction with sodium naphthalenide in MeCN followed by simple purification using the salting-out effect. Their catalytic activity in CuAAC is boosted upon 30 min exposure to air, producing CuO NPs. These NPs are also supported on SBA-15, providing excellent recyclable heterogeneous catalysts that are applied in low amounts for efficient "click" functionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Apart from glycerol, other biosourced alcohol-type solvents like polyethylene glycol (PEG) have been employed in CuAAC reactions [36][37][38][39][40][41][42][43]. In this sense, PEG-400 has been used as environmentally friendly and inexpensive solvent thanks to its: (i) low toxicity; (ii) non-volatility; (iii) recyclability and biodegradability; (iv) thermal stability; and (v) commercial availability [44].…”
Section: Cu-catalyzed 13-dipolar Cycloaddition Of Azides and Alkynes (Cuaac) In Glycerol (Gly)mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from glycerol, other biosourced alcohol-type solvents like polyethylene glycol (PEG) have been employed in CuAAC reactions [36][37][38][39][40][41][42][43]. In this sense, PEG-400 has been used as environmentally friendly and inexpensive solvent thanks to its: (i) low toxicity; (ii) non-volatility; (iii) recyclability and biodegradability; (iv) thermal stability; and (v) commercial availability [44].…”
Section: Cu-catalyzed 13-dipolar Cycloaddition Of Azides and Alkynes (Cuaac) In Glycerol (Gly)mentioning
confidence: 99%
“…Not only CuI, but also the archetypical catalytic mixture CuSO 4 •5H 2 O/ascorbic acid has been fruitfully applied in CuAAC processes devoted to the synthesis of 1,2,3-triazole tethered benzimidazo[1,2-a]quinolines [41] or 1H-1,2,3-triazole tethered pyrazolo [3,4-b]pyridin-6(7H)-ones [42] by employing PEG as sustainable solvent at high temperatures (100-120 • C). Finally, Astruc and co-workers nicely described the use of PEG as stabilizer for copper nanoparticles (CuNP) which are catalytically active in CuAAC processes in a mixture water/ t BuOH and in the presence of air [43]. Scheme 2.…”
Section: Cu-catalyzed 13-dipolar Cycloaddition Of Azides and Alkynes (Cuaac) In Glycerol (Gly)mentioning
confidence: 99%
“…[187][188][189][190][191][192] Supported NPs offer several advantages over the use of unsupported NPs, such as better control of metal dispersion and particle morphology, inhibition of particle aggregation, and generally better reuse of the catalytic system. Given these attributes, different supported and recyclable CuNPs were employed in CuAAC reactions, among the supports employed are alumina, 193 aluminum oxyhydroxide, 194 montmorillonite, 195 MOF, [196][197][198] Cellulose, 199 SBA-15, 200 Zeolite, 201 and more recently graphene oxide. 202 In a study published in 2019 by Gholinejad et al 203 clinochlore was first reported as a very inexpensive and available support for the stabilization of copper nanoparticles and their application as a recyclable catalyst for the formation of 1H-1,2,3-triazoles at room temperature and in aqueous medium.…”
Section: Scheme 25mentioning
confidence: 99%
“…The power of nano—catalysts is proved by their frequent applications in various transformations like oxygen reduction, water oxidation, oxidation of cyclohexenone to phenol, hydrogen generation from formic acid, ultrafast coupling of aryllithium reagents with aryl bromides, Se–Se bond activation, C–O bond activation, one–pot conversion of nitro phenol to benzoxazole, CuAAc reactions, Suzuki–Miyaura coupling, alkyne–cis–semihydrogenation, A 3 –coupling, peptide bond formation, acceptorless dehydrogenative aromatization, selective alcohol oxidation, aerobic oxidation of diaryl and aryl(hetero) methylenes,and C–H bond activation. In spite of these valuable catalytic properties of nanoparticles, there is a significant amount of research is needed to develop methods using economic, cost–effective and readily available non–noble metal nano catalysts.…”
Section: Introductionmentioning
confidence: 99%